2010
DOI: 10.1016/j.jviscsurg.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of recurring subareolar abscess using oncoplastic techniques

Abstract: Our technique is simple and feasible and the results are encouraging. It can be used regardless of the location of the fistula around the periphery of the nipple-areola complex and it is perfectly suited to the management of chronic fistulous abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Among the studies that demonstrated the presence of bacterial infection, both aerobes and anaerobes have been found in the subsequent culturing or sequencing of samples from PDM patients, including Pseudomonas aeruginosa and Staphylococcus aureus [ 12 ]. Although the diversity of bacterial strains which infected the lesions of PDM might be due to different detecting methods and culture media used in different individual study, the overall results still suggest that a specific pathogenic bacterium may not exist for the infection of PDM [ 15 , 16 ]. Therefore, we hypothesize that the main cause of this disease may be the consequent immune response following bacterial infection instead of the infection itself.…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies that demonstrated the presence of bacterial infection, both aerobes and anaerobes have been found in the subsequent culturing or sequencing of samples from PDM patients, including Pseudomonas aeruginosa and Staphylococcus aureus [ 12 ]. Although the diversity of bacterial strains which infected the lesions of PDM might be due to different detecting methods and culture media used in different individual study, the overall results still suggest that a specific pathogenic bacterium may not exist for the infection of PDM [ 15 , 16 ]. Therefore, we hypothesize that the main cause of this disease may be the consequent immune response following bacterial infection instead of the infection itself.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to provide reliable curative treatment for subareolar abscess by initial surgery. This point is illustrated by the use of mastectomy with oncoplastic techniques for recurrent abscess cases [3]. The breast surgeon Lannin [6] reported on the results of treatment that he performed for subareolar abscesses in a 22-year period.…”
Section: Discussionmentioning
confidence: 99%
“…In the remaining half, radical elliptical incision with primary closure resulted in low long-term recurrence rates. Although stable treatment outcomes have been reported by such an experienced surgeon, there are still many cases of recurrent subareolar abscesses due to incomplete treatment [13, 6]. Thus, surgery should be performed after determination of the extent of resection by preoperative imaging evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on the optimal therapeutic strategy for IGM. Surgical removal of the diseased section is the most commonly recommended approach but shows DOI: 10.1159/000503602 more cosmetic problems [6]. Conservative alternatives include close observation, antibiotics, or immunosuppressive therapy with corticosteroids.…”
Section: Introductionmentioning
confidence: 99%